2017
DOI: 10.1039/c6ra25998g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of chitosan biguanidine hydrochloride and its regulation on InsR and GLUT2 in insulin resistant HepG2 cells

Abstract: CSGH increased glucose consumption of HepG2 cells by accelerating the expression of InsR and inhibiting the high-insulin-induced over-expression of GLUT2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…28,47 From this standpoint, the crosslinking action of CSGH and its coating on the WPU surface can be considered as the reasons for the increase of particle size. Besides, our previous research also reported that CSGH is more hydrophilic and blending WPU/CSGH ((e) Sample E) films surface than chitosan, 32,33 and its interaction with water is enhanced. As a result, the viscosity of CSGH-WPU was also significantly increased.…”
Section: Emulsion Propertiesmentioning
confidence: 78%
See 2 more Smart Citations
“…28,47 From this standpoint, the crosslinking action of CSGH and its coating on the WPU surface can be considered as the reasons for the increase of particle size. Besides, our previous research also reported that CSGH is more hydrophilic and blending WPU/CSGH ((e) Sample E) films surface than chitosan, 32,33 and its interaction with water is enhanced. As a result, the viscosity of CSGH-WPU was also significantly increased.…”
Section: Emulsion Propertiesmentioning
confidence: 78%
“…CSGH was prepared based on our previous report. 32,33 The synthetic process of CSGH is shown in Figure 1.…”
Section: Synthesis Of Csghmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Therefore, more efforts should be devoted to developing natural medicines without side effects or toxicity. [25,26] Furthermore, COSG can inhibit high glucoseinduced activation of the DAG/PKC pathway by regulating the expression of GLUT-2, with measurable nephroprotection in the early stage of experimental DN in rats. [22] COS improves the altered blood glucose metabolism in diabetic rats by accelerating the proliferation/neogenesis of β-cells and insulin secretory capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that chitosan guanidine hydrochloride (CSGH) and chitooligosaccharide biguanide (COSG) can control glucose uptake by regulating the in vitro expression of glucose transporters (GLUTs), suggesting that these molecules are efficient in modulating blood sugar and improving glucose metabolism . Furthermore, COSG can inhibit high glucose‐induced activation of the DAG/PKC pathway by regulating the expression of GLUT‐2, with measurable nephroprotection in the early stage of experimental DN in rats .…”
Section: Introductionmentioning
confidence: 99%